Long Waves of Strikes in South Africa: 1886"“2019 - Cottle, Eddie (Rhodes University, Faculty of Humanities, Institute of Social and Economic Research, 2020)
This thesis is underpinned by a single question: What combination of factors gives rise to and produces turning point strikes and turning point strike waves? The thesis contends that long wave theorists have neither examined the combined effect of the escalation of the class struggle, the characteristics of the structural effects of strike waves and the types of labour turning points, nor explained how the theory accounts for the general movement towards the intensification of strikes and strike waves. To counteract this shortcoming in long wave theory, and in the absence of a general theory of strikes or a standardised method to study strike dynamics, this thesis employed strike statistics, econometrics, and economic and labour history to identify the short- and long-term patterning of strikes and strike waves over long periods (1886–2019) of expansion and contraction of the capitalist economy. While the findings of this thesis confirm Mandel’s theory that the trigger of initial strike waves is a clustering of cost-cutting technological innovations and changes to the labour process, they, more importantly, demonstrate that it is the combination of other dynamics – business cycle fluctuations, long-standing grievances, levels of mobilisation capacity and political factors that culminate in strike waves and have structural effects – that intensify the class struggle. The central contribution of this thesis is the introduction of the concepts of a turning point strike, an initial rupture and a turning point strike wave that combine to produce structural change. These enable an understanding of the general movement of strikes, from an initial turning point strike wave that signals the deepening and broadening of the class struggle and results in structural effects that lead to increased levels of labour mobilisation and changes in industrial relations, to a historical turning point strike wave that ushers in political reforms, revolution or defeat of the working class, leading to a political turning point. This then marks changes in political representation and economic and social policy. The thesis concludes that turning point strike waves follow a specific patterning, making it possible to predict the next round of turning point strike waves globally.
Keywords: Strikes and lockouts -- South Africa; Long waves (Economics) -- South Africa; Business cycles -- South Africa; Industrial mobilization -- South Africa; Collective bargaining -- South Africa; Institutionalisation; Labor unions -- South Africa